Hotel maintenance management in Sanya, China. Issue 4 (5th September 2016) - Pitt, Michael; Cannavina, Dominique; Sulaiman, Raha; Mahyuddin, Norhayati; Wu, Cenlang
Abstract : Purpose: To optimize hotel maintenance works, planned and reactive techniques are required which efficiently and effectively engage with the commercial and regulatory requirements of hotel operators and maintenance managers. The purposes of this study are to identify the constraints and challenges of hotel maintenance from the viewpoints of key stakeholders and to determine the strategies and processes employed in maintenance to overcome them. Design/methodology/approach: The study focuses on five and four star hotels in Sanya of the Hainan Province. Eight face-to-face interviews were conducted in conjunction with 50 questionnaires, which were distributed to senior hotel operators and maintenance managers. Findings: Maintenance management strategies are collaborative, with input from multiple stakeholders. Partial outsourcing is extremely common, being employed as a way of lowering operating costs and saving time while also meeting governmental statutory and regulatory requirements for some mechanical and electrical services. Availability of skilled workers, types of systems being serviced and the availability of specialist materials and tools were all found to influence the viability and effectiveness of in-house maintenance as discrete from outsourced maintenance. In reality, the challenges can include a lack of labor training and relatively lower quality of materials or energy efficiency requirements, especially in Sanya's hotel industry. Originality/value: The aim of this research was primarily focused on identifying the present maintenance statuses and strategies in hotels while determining the factors which result in a favorable bias toward a successful hotel maintenance management. Factors that affect hotel operators' and maintenance managers' decisions were identified and their influences quantified. The difficulties faced by hotels in implementing maintenance strategies were ratiocinated and stated to investigate those issues more deeply.